Performance of public sector infrastructure projects in Pakistan : the role of project governance through stakeholder management and benefit management - Khan, Asadullah (2019)
Project governance, benefit management, and stakeholder management have been acknowledged as a means of increasing the probability of successful delivery of projects, but its full functions have yet to be explored for the performance of public sector infrastructure projects. The governance of public sector projects became an important topic of interest in the project, program, and portfolio management literature during the last decade. Today, it is becoming a central focus for policymakers to ensure success in selecting, designing, and implementing government-sponsored programs. Due to the complexities, the governance of infrastructure programs constitutes a critical element in strategic planning in developing countries. This study has analyzed the performance of public sector infrastructure projects in Pakistan. The overall aim of this study is to explore the role of project governance in the performance of public sector project through benefit management and stakeholder management. In this study, a thorough literature review is conducted to investigate the performance of the projects. The research uses a positivist approach and quantitative design. The quantitative technique is employed to address all the aspects of the study. Stratified random sampling is followed in this research. Different statistical techniques, i.e. reliability and validity assessment, descriptive analysis, normality test, and correlation are used to analyse the data. Based on the relevant theories, a conceptual framework is developed and an empirical investigation is carried out among professionals of the Planning Commission of Pakistan and provincial Planning and Development Departments. Structural equation modeling is the core statistical technique for testing the model and hypotheses. The findings of this study indicate that mediation and moderation of benefit management and stakeholder management respectively, in the relationship of project governance and project performance helps in improving the overall performance of public sector infrastructure projects i.e. the results have confirmed that benefit management and stakeholder management has a positive effect on the relationship of project governance and project performance. This study contributes to the stakeholder theory and transaction cost theory. The study contributes to the literature as the findings show that dimensions of project governance can be benefited from the stakeholder theory, which can enhance project performance. The study offers insights to the transaction cost theory approach and provides empirical work that helps decision-makers in the development process. Practically, this research can serve as a roadmap for effective project governance for the performance of public sector infrastructure projects. The main recommendation of this study is that the public sector infrastructure development projects should invest and adopt a project governance mechanism to achieve its goals and success. It is essential for the development projects in Pakistan to attain potential future benefits. Keywords: Project governance, benefit management, stakeholder management, project performance, public sector.